Intussusception secondary to inflammatory myofibroblastic tumor of the small intestine. Case report - David Yépez-Yépez; Lúver Macías-Jara; Betsy Macías-Jara (Case Reports)
Introduction: Intussusception occurs when part of the intestine slides into an adjacent intestinal segment. Inflammatory myofibroblast tumor is a rare cause of this condition, and is observed in 5% -16% cases in adults.